Tunable 2.0 μm Q-switched fiber laser using a silver nanoparticle based saturable absorber - Ahmad, H.; Samion, M. Z.; Muhamad, A.; Sharbirin, Anir Syazwan; Shaharuddin, R. A.; Thambiratnam, Kavintheran; Norizan, Siti Fatimah; Ismail, Mohammad Faizal (Maik Nauka-Interperiodica Publishing, 2017)
A thulium-doped fiber laser (TDFL) with a tunable Q-switched output is proposed and demonstrated. A silver nanoparticle based saturable absorber is used to generate the Q-switched pulses, while a tunable Mach-Zehnder filter acts as the wavelength-tuning mechanism. The TDFL has an operating wavelength range of 1916.5-1945.3 nm, with output pulses that have a repetition rate of 50.1 kHz and a pulse width of 5.1 μs, as well as a pulse energy of 69.3 nJ at the maximum pump power. The Q-switched pulses obtained are very stable and have a signal-to-noise ratio of 34.18 dB.